The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/poms.12829
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Operational Predictors of Future Financial Distress in the US Airline Industry

Abstract: We investigate the predictive power of operational performance on future financial distress in the context of the US airline industry. We focus on four areas of operational performance: revenue management, operational efficiency, service quality, and operational complexity. Using quarterly data from 1988 through 2013, we find that airlines that have inferior revenue management, lower aircraft utilization, and higher operational complexity face higher future financial distress. Interestingly, average service qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Operational Efficiency. Operational efficiency is the relative efficiency of a firm in its ability to convert organizational resources into business outcomes in comparison with its industry peers (Peng et al, 2008;Alan and Lapré, 2018;Chuang et al, 2019). We use the stochastic frontier estimation (SFE) methodology to measure a firm's operational efficiency in transforming its resources such as the number of employees (EMP), capital expenditure (CEX), and inventory (INV) into its operating income (OI), and measure the efficiency of each firm relative to its competitors in the same industry (Dutta et al, 2005;Li et al, 2010).…”
Section: Measurementsmentioning
confidence: 99%
“…Operational Efficiency. Operational efficiency is the relative efficiency of a firm in its ability to convert organizational resources into business outcomes in comparison with its industry peers (Peng et al, 2008;Alan and Lapré, 2018;Chuang et al, 2019). We use the stochastic frontier estimation (SFE) methodology to measure a firm's operational efficiency in transforming its resources such as the number of employees (EMP), capital expenditure (CEX), and inventory (INV) into its operating income (OI), and measure the efficiency of each firm relative to its competitors in the same industry (Dutta et al, 2005;Li et al, 2010).…”
Section: Measurementsmentioning
confidence: 99%
“…These findings are supported by Jacobs et al [47], who showed that more productive firms can experience less cost and more profits, and better performance in a lower bankruptcy risk and larger market value. In addition to the manufacturing industry mentioned above, the transportation industry was another research area in the previous literature [48,49]. For instance, fleet utilization and the fuel efficiency rate were used as cost-based efficiency measures and replace the roles of costs and waste in the manufacturing industry [48].…”
Section: Efficiency and Financial Performancementioning
confidence: 99%
“…In addition to the manufacturing industry mentioned above, the transportation industry was another research area in the previous literature [48,49]. For instance, fleet utilization and the fuel efficiency rate were used as cost-based efficiency measures and replace the roles of costs and waste in the manufacturing industry [48]. As reducing unnecessary costs aims to provide goods and services with minimum waste and maximum utilization of resources, we propose the following hypothesis:…”
Section: Efficiency and Financial Performancementioning
confidence: 99%
“…Predicting binary events is a deeply researched topic in finance, for instance to predict bankruptcy or financial distress (Sarkar andSriram 2001, Alan andLapré 2018), but now it is also becoming more common in other areas, including supply chain management. In fact, predicting unauthorized subcontracting was the original motivation of the middleman M. that sparked this research project.…”
Section: Predictionmentioning
confidence: 99%